Production of xylanase by a new strain of Thermoascus aurantiacus: obtainment of enzymatic extract with reduced cellulolytic activity for application in pulp and paper industries - Ana Carolina da Costa; Rodrigo Prudente Scalabrini; Maria Alice Silvestre; André Rodrigues; Marcelo Fossa da Paz; Gustavo Graciano Fonseca; Rodrigo Simões Ribeiro Leite (Bioscience Journal, 2016)
Xylanases are useful in several industrial segments, including pulp and paper bleaching, animal feed, and bread-making processes. However, the industrial use of these enzymes is closely related to its production cost and its catalytic properties. The process of solid state fermentation enables the use of agro-industrial residues as substrates for microbial cultivation and enzymes production, reducing costs. In the present study, different cultivation parameters were evaluated for the xylanase production by the thermophilic fungus Thermoascus aurantiacus, by solid state fermentation, using agro-industrial residues as substrates. High production of xylanase (1701.9 U g-1 of dry substrate) was obtained using wheat bran containing 65% of initial moisture, at 120 h of cultivation, and 45°C. The xylanase showed optimal activity at pH 5.0 and 75°C; its stability was maintained at pH 3.0-11.0. The enzyme retained its catalytic potential after 1 h, at 75°C. The enzymatic extract produced under optimized conditions showed reduced activities of endoglucanase and FPase. Our results, including the xylanase production by T. aurantiacus in low-cost cultivation medium, high structural stability of the enzyme, and reduced cellulolytic activity, encourage the application of this enzymatic extract in pulp and paper bleaching processes.